Professional Training of New Farmers: The Case of Students of the American Farm School’s Private Vocational Training Institute - Anna Papakonstantinou; Marios Koutsoukos; Konstantinos Zoukidis; Evangelos Vergos (Emerging Issues in Agricultural Sciences Vol. 9, 2023)
The goal of this study is to learn more about how young farmers perceive various aspects of vocational education as they relate to American Farm School students enrolled in the Vocational Training Institute (VTI). The intent of vocational education is to prepare students for careers as technologists, craftspeople, or tradesmen. Another way to think about vocational education is as the kind of education that is given to a person in order to provide them with the required skills for gainful work or self-employment. Processed data arriving from specially formulated Likert level questions revealed that young farmer students find it absolutely necessary to participate in training programs governed by experiential learning methodologies, while recognizing that these processes are linked to their knowledge and skill improvement for developing a firm future professional consignment in the agrofood sector. To that extend, experiential learning applications would subsequently assist program participants to cultivate and grow a better understanding for innovation, which undoubtedly affect the path of agribusiness investment sustainability. Although current national sectorial progress has taken significant steps ahead, seems that still not being satisfactory in terms of competitiveness. However, there has to be always tension to gradually execute such methods of professional experiential learning from specialized educational organizations to concretely reach out higher levels of improvement in rural development alongside with other important eminent and specialized factors.